Planning a competence‐based curriculum: the case of four secondary schools in England. Issue 3 (1st September 2013) - Byrne, Jenny; Downey, Christopher; Souza, Ana
Abstract : Despite the belief that schools tend to be resistant to change, it is possible to find secondary schools in the UK which are investing in the design of an innovative curriculum for their Year 7 (11‐year‐old students). This article focuses on four of these schools and discusses some of the challenges they face in planning and implementing their competence‐based curricula (CBC). Such curricula tend to be based on the rationale that they better prepare all students for the constant changes of human knowledge and understanding. They develop transferable skills rather than subject‐specific content, which are considered necessary requirements for learners as future productive members of society in the twenty‐first century. Advocates of CBC argue that such curricula are more inclusive and emancipatory than traditional curricula, although this view is contested. Employing Bernstein%s concepts of framing and classification of the curriculum, this article describes the challenges and constraints encountered by four schools which have endeavoured to develop a competence‐based curriculum.